2016
DOI: 10.1016/j.ebiom.2016.10.029
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for Acute Electrophysiological and Cognitive Changes Following Routine Soccer Heading

Abstract: IntroductionThere is growing concern around the effects of concussion and sub-concussive impacts in sport. Routine game-play in soccer involves intentional and repeated head impacts through ball heading. Although heading is frequently cited as a risk to brain health, little data exist regarding the consequences of this activity. This study aims to assess the immediate outcomes of routine football heading using direct and sensitive measures of brain function.MethodsNineteen amateur football players (5 females; … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

19
153
3
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 122 publications
(177 citation statements)
references
References 31 publications
19
153
3
2
Order By: Relevance
“…Repetitive head impacts reported in soccer athletes have associations with neuropsychological impairment as well as abnormal white matter microstructure (Koerte, Ertl-Wagner, Reiser, Zafonte, & Shenton, 2012; Lipton et al, 2013), structural brain changes (Adams, Adler, Jarvis, DelBello, & Strakowski, 2007; Sortland & Tysvaer, 1989), and electro-physiological changes (Di Virgilio et al, 2016). Of these studies, there is a suggestion that the types of neuropsychological function impacted may vary depending on the duration of the exposure.…”
Section: Introductionmentioning
confidence: 99%
“…Repetitive head impacts reported in soccer athletes have associations with neuropsychological impairment as well as abnormal white matter microstructure (Koerte, Ertl-Wagner, Reiser, Zafonte, & Shenton, 2012; Lipton et al, 2013), structural brain changes (Adams, Adler, Jarvis, DelBello, & Strakowski, 2007; Sortland & Tysvaer, 1989), and electro-physiological changes (Di Virgilio et al, 2016). Of these studies, there is a suggestion that the types of neuropsychological function impacted may vary depending on the duration of the exposure.…”
Section: Introductionmentioning
confidence: 99%
“…The message is that concussion is a dangerous condition that causes a complex neuropsychiatric disorder, chronic traumatic encephalopathy (CTE), with a neuropsychiatric phenotype of mood change, irritability and suicidal behaviour which develops over time into a neurodegenerative disorder and death 1. Increasing alarm has followed, and it has been suggested that this is not just a disorder of elite sportsman but a problem for youth sport and that even heading a football (soccer) may cause dementia,2 a terrifying prospect for those parents trying to decide whether to allow their children to participate in sports.…”
Section: A Little Less Conversation a Little More Science Pleasementioning
confidence: 99%
“…However, these limitations should not detract from the novel and innovative study presented by Di Virgilio et al (2016). Indeed the evidence from this study demonstrates that repeat sub-concussive head impacts affect the brain physiologically.…”
mentioning
confidence: 78%
“…To address the issue of measuring the direct functional outcome effects of sub-concussion, Di Virgilio et al (2016) utilize the technique of single-pulse transcranial magnetic stimulation (TMS). A well-established and non-invasive technique to measure motor threshold, corticospinal conduction time, motor cortex excitability and intracortical inhibition (Kobayashi and Pascual-Leone, 2003), TMS has been used previously to determine neurophysiological changes following acute concussion events (Pearce et al, 2015) as well as long-term chronic neurological impairments in contact sport athletes with a history of multiple concussions (Pearce et al, 2014, Major et al, 2015).…”
mentioning
confidence: 99%
See 1 more Smart Citation